Optimizing the Health of Pregnant Women with Socialization of Anemia Prevention and Giving Blood Supplement Tablets to Pregnant Women - Fadhlurrohman, Irfan; Maharani, Ghina Adibah; Nawar, Nazmi; Alhamidi, Alfin Faiz; Muthi, Sherlyta Nisrina; Salsabila, Naila Azhari; Sagita, Rossanna Aulia Fitri; Azka, Pentherro Fadhlin Kaesar; Daud, Muhammad Isa; Putri, Dinar Dwi Anindya; Alfaenah, Afna; Kosanti, Hilari Dea (International Journal of Community Service (IJCS), 2025)
Anemia in pregnant women remains an important public health issue in Indonesia. This condition can lead to adverse effects for both the mother and the fetus, including risks of preterm birth, low birth weight, and even mortality. This research seeks to improve pregnant women’s awareness of anemia and significance of taking Iron and Folic Acid Tablets (IFA) by utilizing an educational method. The method employed involved lectures supplemented by pre-test and approach used included lectures along with pre-test and post-test evaluations. The findings indicated a notable increase in post-test scores incomparison to the pre-test, indicating that the lecture method was effective in delivering health information. In addition to education, this activity also involved the distribution of IFA tablets to pregnant women as a concrete step in preventing anemia. The lecture approach proved to be an effective promotive and preventive strategy in improving maternal health.